Інноваційні складові транспортних процесів вантажних перевезень у галузі автомобільного транспорту - Гайкова, Т. В.; Загорянський, В. Г.; Солошич, І. О.; Haikova, T.; Zahorianskyi, V.; Soloshych, I. (ЦНТУ, 2023)
У статті розглядаються ключові компоненти організації інноваційної діяльності у сфері автомобільного транспорту вантажних перевезень. У сучасному світі інновації стали невід’ємною та необхідною частиною функціонування цієї галузі, і тому важливо вивчати, обговорювати та систематично розглядати їх. Фундаментальним елементом є осередок, на якому базується інноваційна активність, тому важливо регулярно висвітлювати та розширювати його контекст. Based on the analysis of scientific and technical information, it was established that road transport is one of the most important components of the country's economy. Transport connects different regions, enterprises and branches of the national economy, plays a huge role in the location of enterprises and factories and is an important condition for the rational location of production. Despite this, the use of road transport technologies at the current stage is associated with a number of serious problems that need to be solve at the technological level. The most important and promising direction in the complex solution of existing problems in road transport is the development and use of the latest innovative technologies, the rapid development of which creates practically unlimited prospects for road transport.
Innovative components of transport processes of freight transportation in the field of road transport
Keywords: інновація; транспортні процеси; автомобільний транспорт; вантажні перевезення; екологічна безпека; innovation; transport processes; automobile transport; cargo transportation; ecological safety